2021
DOI: 10.1155/2021/1928383
|View full text |Cite
|
Sign up to set email alerts
|

Modulus Inversion Layer by Layer of Different Asphalt Pavement Structures

Abstract: In order to improve the accuracy of modulus inversion of the pavement structure layer, a layer-by-layer inversion method was proposed to be compared with the traditional inversion method by inverting the modulus of each structural layer of the inverted asphalt pavement and semirigid asphalt pavement. The results show that the influence of cushion modulus on the modulus of inverted subgrade and modulus of cement-stabilized crushed stone is restricted by the cushion modulus and pavement structure characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Based on the displacement measurement of the soft body impact of aluminum plate, Yu et al [9] used BP neural network to invert the bird composition model and showed that the proposed inversion model is more reasonable. Cao et al [10] improved the accuracy of inversion of modulus of each structural layer of asphalt by layer-by-layer inversion method to provide a basis for research. Luo et al [11] used the measured data, combined with GA-BP neural network, to calculate the mechanical parameters of the surrounding rock by displacement inverse analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the displacement measurement of the soft body impact of aluminum plate, Yu et al [9] used BP neural network to invert the bird composition model and showed that the proposed inversion model is more reasonable. Cao et al [10] improved the accuracy of inversion of modulus of each structural layer of asphalt by layer-by-layer inversion method to provide a basis for research. Luo et al [11] used the measured data, combined with GA-BP neural network, to calculate the mechanical parameters of the surrounding rock by displacement inverse analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, central deflection can characterize the overall strength of asphalt pavement. Distal deflection can characterize the subgrade strength, and the difference between the maximum deflection 2 of 14 and distal deflection can characterize the tensile stress of the bottom structural layers of asphalt pavement [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sargand et al [10] relied on Ohio test track permanent asphalt road interview section WAY-30 to test the effects of speed, load (biaxial 179 kN and uniaxial 125 kN), and load offset on the dynamic response of asphalt pavement at high and low temperatures, but the axle load and pavement structure form are relatively single. Cao et al [11,12] analyzed the deflection and modulus characteristics of inverted asphalt pavement and semirigid asphalt pavement based on FWD measured deflection basin data. Assogba et al [13] studied the strain response law of the bottom of each asphalt layer in the pavement structure by combining numerical simulation and field test, and overloading can lead to extremely unfavorable fatigue life of semirigid asphalt pavements.…”
Section: Introductionmentioning
confidence: 99%